The Effect of the Use of Electronic Commerce and User Work Effectiveness on Business Performance in Publishing Businesses in Bandung Regency - M Iffan; P W Suhendar (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the effect of the use of e-commerce and user work effectiveness on business performance, either partially or simultaneously. This research was conducted at various book publishers in Bandung Regency, Indonesia. The population in this study were 23 book publishers. The sampling technique used in this study is a saturated sampling technique. Based on the variables studied, this type of research is descriptive and verification. While the analytical method used is multiple linear regression analysis, correlation coefficient analysis, analysis of the coefficient of determination, and hypothesis testing either partially or simultaneously. The results of this study indicate that the use of e-commerce has no significant effect on business performance partially due to the unavailability of experts to optimize the use of e-commerce and some book publishers still focus on selling books offline, but user work effectiveness has a significant effect on business performance. Simultaneously, the use of e-commerce and the effectiveness of users’ work have a significant effect on business performance. The results also show that the independent variables in this study can be applied in improving the business performance of book publishers. The conclusion of this study is expected to help business owners to be able to develop their business by maximizing sales both online and offline, and can personalize online sales media to provide convenience, comfort, and security to consumers in transacting